Application of the CFD Method to the Study of Safety in Mining - Based on a Systematic Literature Review - Dorota PALKA (Communications of International Proceedings, 2021)
The purpose of this publication is to review and analyze the development of the CFD method, to determine the areas of its application in mining, in particular in the field of ventilation, taking into account natural hazards such as fire, gas or dust hazards. A systematic literature re-view was adopted as the research method. According to the book's definition, it is a transparent and systematic literature research conducted in accordance with the applicable rules and criteria. The methodology is described in one part of the article. As a result of the literature analysis, the answers to three main questions were answered by researchers: (1) In what scientific areas has the CFD method been used in recent years and how has it changed over the last decade? (2) In which areas has CFD been used in mining and how has this changed in the last 10 years? (3) What is the significance and role of the CFD method in mining and what are the directions of its further application in this industry? Also, on the basis of the conducted analysis, it was found that, despite many available publications, no similar work has been published. This indicates the need for further research in this field in order to clarify the research area.
Keywords: Systematic Literature Review; CFD Method; Mining; Methane